Pengaruh Enterprise Risk Management, Financial Risk, dan Carbon Emission Disclosure Terhadap Nilai Perusahaan - Aryan Rhakasa Putra Setiadi, Mohamad; Widiyati, Dian (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2025)
This study aims to determine and analyze the influence of Enterprise Risk Management, Financial Risk, and Carbon Emission Disclosure on Company Value in industrial sector companies listed on the Indonesia Stock Exchange for the period 2021 to 2023. This type of research is quantitative research, using secondary data. The data analysis methods used are descriptive statistical tests, panel data model analysis, classical assumption tests and hypothesis tests using Microsoft Excel and E-Views 12 applications. The population in this study is industrial sector companies listed on the Indonesia Stock Exchange for the period 2021 to 2023. The data collection technique in this study is a purposive sampling technique with a total of 66 populations, so that the data samples obtained in this study are 12 samples. The results of the study show that Enterprise Risk Management, Financial Risk, and Carbon Emission Disclosure simultaneously affect the Company's Value. Then, the results of the study partially stated that Financial Risk and Carbon Emission Disclosure had a negative influence on the Company's Value. Meanwhile, Enterprise Risk Management has no effect on the Company's Value.